Transcriptome Analysis of Hamelia patens (Rubiaceae) Anthers Reveals Candidate Genes for Tapetum and Pollen Wall Development - Yue, Lin; Twell, David; Kuang, Yanfeng; Liao, Jingping; Zhou, Xianqiang (Frontiers in Plant Science, 2017)
Studies of the anther transcriptome on non-model plants without a known genome are surprisingly scarce. RNA-Seq and digital gene expression (DGE) profiling provides a comprehensive approach to identify candidate genes contributing to developmental processes in non-model species. Here we built a transcriptome library of developing anthers of Hamelia patens and analysed DGE profiles from each stage to identify genes that regulate tapetum and pollen development. In total 7,720 putative differentially expressed genes across four anther stages were identified. The number of putative stage-specific genes was: 776 at microspore mother cell stage (MMC), 807 at tetrad stage (TET), 322 at uninucleate microspore stage (UNM) and the highest number (1,864) at bicellular pollen stage (BCP). GO enrichment analysis revealed 243 differentially expressed and 108 stage-specific genes that are potentially related to tapetum development, sporopollenin synthesis and pollen wall. The number of expressed genes, their function and expression profiles were all significantly correlated with anther developmental processes. Overall comparisons of anther and pollen transcriptomes with those of rice and Arabidopsis together with the expression profiles of homologs of known anther-expressed genes, revealed conserved patterns and also divergence. The divergence may reflect taxon-specific differences in gene expression, the use RNA-seq as a more sensitive methodology, variation in tissue composition and sampling strategies. Given the lack of genomic sequence, this study succeeded in assigning putative identity to a significant proportion of anther-expressed genes and genes relevant to tapetum and pollen development in H. patens. The anther transcriptome revealed a molecular distinction between developmental stages, serving as a resource to unravel the functions of genes involved in anther development in H. patens and informing the analysis of other members of the Rubiaceae.